IMPLEMENTASI UUPPLH TERHADAP PERLINDUNGAN LINGKUNGAN HIDUP DALAM PERSPEKTIF SIYASAH SYAR’IYYAH: Studi Pada Pabrik Kelapa Sawit - Nurdin, Ina Adriana; Suryadi, (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
Environmental protection is an effort made in order to preserve environmental functions and also prevent environmental damage. Based on this, the main problems that will be described in sub-problems are as follows: (1) How is the implementation of environmental protection after the ratification of the Job Creation Act? (2) How is the impact of palm oil mills on the environment in East Luwu? (3) What is the perspective of siyasah syar'iyyah on environmental protection?. This research is a field qualitative research using a syar'i normative approach and a statutory approach. The results showed that the implementation of environmental protection after the work creation law was ratified had been carried out well, namely by obtaining environmental permits accompanied by the management of Amdal documents and UKL-UPL letters that had been approved by the Central Government or Regional Governments and the latest with the approval of the community. local. Palm oil mills as one of the industries that play a very important role in the regional economy by opening up job opportunities and facilities that can be enjoyed by the local community apparently have an unfavorable impact on the health and comfort of the people living around the palm oil mill. So that the role of local governments is needed in maintaining the environment so that it remains sustainable.